Detection of mosaic variants using genome sequencing in a large pediatric cohort. Issue 3 (23rd December 2022) - Odgis, Jacqueline A.; Gallagher, Katie M.; Rehman, Atteeq U.; Marathe, Priya N.; Bonini, Katherine E.; Sebastin, Monisha; Di Biase, Miranda; Brown, Kaitlyn; Kelly, Nicole R.; Ramos, Michelle A.; Thomas‐Wilson, Amanda; Guha, Saurav; et al.
Abstract: The increased use of next‐generation sequencing has expanded our understanding of the involvement and prevalence of mosaicism in genetic disorders. We describe a total of eleven cases: nine in which mosaic variants detected by genome sequencing (GS) and/or targeted gene panels (TGPs) were considered to be causative for the proband's phenotype, and two of apparent parental mosaicism. Variants were identified in the following genes: PHACTR1, SCN8A, KCNT1, CDKL5, NEXMIF, CUX1, TSC2, GABRB2, and SMARCB1 . In addition, we identified one large duplication including three genes, UBE3A, GABRB3, and MAGEL2, and one large deletion including deletion of ARFGAP1, EEF1A2, CHRNA4, and KCNQ2 . All patients were enrolled in the NYCKidSeq study, a research program studying the communication of genomic information in clinical care, as well as the clinical utility and diagnostic yield of GS for children with suspected genetic disorders in diverse populations in New York City. We observed variability in the correlation between reported variant allele fraction and the severity of the patient's phenotype, although we were not able to determine the mosaicism percentage in clinically relevant tissue(s). Although our study was not sufficiently powered to assess differences in mosaicism detection between the two testing modalities, we saw a trend toward better detection by GS as compared with TGP testing. This case series supports the importance of mosaicism in childhood‐onset genetic conditions and informs guidelines for laboratory and clinical interpretation of mosaic variants detected by GS.